Genealogies of Ghana’s housing crisis: the role of colonial interventions and neoliberal reforms - Addo, I.A.; Mba, C.C. (Taylor & Francis Group, 2021)
The urgent need to develop and increase housing units has always featured prominently in electioneering campaigns in Ghana. Successive governments have developed countless programmes to deal with the housing deficit, but there has not been a significant improvement. As we write, the government of Ghana is grappling with a housing deficit of over two million units. But why has this problem remained intractable despite what seems like concerted efforts by various administrations to provide affordable housing for Ghana’s more vulnerable populations? Focusing on the 2015 National Housing Policy, this article critically reviews Ghana’s various housing policies and reforms, exploring how colonial policies and neoliberal reforms are separately and jointly implicated, in fundamental ways, in Ghana’s currently engulfing housing crisis. Our findings reveal that the yawning gap noticeable in Ghana’s overall effort at housing provision for the populace, is rooted in the colonial logic of piecemeal intervention. This same logic has continued to traverse successive Ghanaian housing policies through the immediate postcolonial era, the adjustment years, and the current period.
Research Article
Keywords: Colonialism; Ghana; Ghana’s housing policy; neoliberal reforms; piecemeal intervention